Insertion and professional development of starting university professors: the need for spaces for pedagogical discussion - Beatriz Maria Boessio Atrib Zanchet; Nadiane Feldkercher (Universidade Estadual de Maringá, 2016)
Current paper is the result of a research on twenty-eight starting university teachers in four universities in southern Brazil and seeks to understand their concern on pedagogical discussion spaces as a possible support for the development of their teaching practice. The research started from the point that starting teachers should insert themselves within higher education culture and find pedagogical support to develop their lectures. As a rule, they have recently obtained a doctoral degree, complying with the required academic title for their tenure, but with scanty or no pedagogical preparation. The subjects answered a semi-structured interview, with issues on the challenges, difficulties and possibilities of pedagogical support pointed out when they started their activities. The quantitative data form the corpus analyzed used in the analysis. The paper is based on studies by Garcia (1999, 2009b), Vaillant and Garcia (2012) and others. Results showed that pedagogical education and professional development of university professors, developed through pedagogical spaces, are essential for and welcomed by these teachers. An overall policy is required that valorizes the teaching tasks as fundamental for achieving teaching quality.